Development and validation of an instrument to measure science teachers’ instructional preparedness in stem implementation - Ramli, Nur Farhana (2019)
STEM has gained increased attention in recent years as the government is trying to prepare students for the demand of future workforce. It is also an effort to produce literate citizens who can solve problems in the context of daily life, society and environment using the application of knowledge, skills and STEM values. The failure of the previous policy had found that instructional teacher is one of the aspects that causes students to be less interested in STEM. As the new STEM curriculum has been introduced in Malaysia's education system recently, it is need to build an instrument that measure the level of teachers’ instructional preparedness in order to assist the success of National Education aspirations, especially in STEM education. Thus, the STEM Instructional Preparedness Instrument (STEMTIP) was developed to test the teacher's instructional preparedness in STEM implementation. This study was divided into two phases which are development phase and validation phase. In the development phase, the conceptualisation and items were generate using both inductive and deductive approaches. With the help of four teachers that were involved in focus group discussion and also information from literature review, 51 items we generated. The items were then were tested during the second phase of the study by conducting reliability tests, face validation, content validation, construct validation and criterion validation. In face validation, five science teachers were selected to verify the language and the clarity of the items. As for content validation, 15 experts have been involved to determine the items content validation. Through content validation testing using the Lawshe Model, 47 items have gained expert consensus, however, the remaining four items were maintained during the next test with some refinement. Field studies were then conducted on 265 science teachers in Malaysia using randomised multistage cluster sampling. STEMTIP was identified to have excellent reliability and replicability through the findings of Cronbach alpha (.98), person reliability (.96) and item reliability (.98). Construct validation was determined using Rasch Model. The analysis found that the instrument has unidimensionality, local independence, polarity, excellent separation indices and effective scale. However, 10 misfit items were removed from the instrument as they showed disturbance feature in measurement. Misfit items indicate a lack of consistency in interpreting the underlying measure that requires the need for further study in the future research. Also, two items were identified as having potential biased based on the school location but were kept remained as it will be useful for stakeholder future undertaking. Criterion tests found that STEMTIP was able to contribute 40.6% to teachers' self-efficacy in STEM implementation. Overall, based on all tests, this instrument has been proven to be a good instrument. The researchers are confident that the STEMTIP instrument has passed psychometric standards and can be used by stakeholders to measure instructional preparedness of STEM teachers.